Nonlinear static stiffness of rail pads for different materials and thicknesses using finite element method / Arif Khuarizmi Mazlan ... [et al.] - Mazlan, Arif Khuarizmi; Abdul Wahab, Abdul Malek; Anuar, Muhamad Azhan; Makhtar, Ahmad Khushairy (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
The rail pad located in between the steel rail and base plate provides flexibility to the track and cushions from shocks and vibrations resulting from train operation. This polymeric material has nonlinear behaviour. In this study, the behaviour of the rail pad for different polymeric materials and various thicknesses was investigated. The three different types of rail pads were ethylene propylene diene monomer (EPDM), thermoplastic elastomers (TPEs) and ethylene vinyl acetate (EVA). Three-dimensional (3D) finite element (FE) approach was used to model the fastening system under the static load. The Abaqus software was used for the FE analysis. The thicker rail pad deformed more than the thinner for the same load value. Comparing the thickness, EPDM pad had the highest amount of deformation which had an average difference of 40%, followed by TPE and then EVA with 33% and 23% respectively. The static stiffness of EVA material was the highest followed by TPE and EPDM. For all materials, the rail pad became stiffer as thickness decreased. The reaction force decreased as the thickness of the rail pad increased. EVA, TPE and EPDM showed 15%, 9% and 5% reduction of reaction force respectively as the rail pad thickness increased from 5 mm to 10 mm. Despite that, in term of material, EVA had highest capability to reduce reaction force compared to EPDM and TPE.